INCREASE IN PURCHASING SWCISIONS FOR NEXIAN PHONE THROUGH PRICE, PRODUCT QUALITY AND EASE OF USE ONLINE AT THE LAZADA SITE (Case Study Of STIE AUB Surakarta Students) - Nuryati Nuryati; Afifka Nur’ Aini (STIE AUB Surakarta, 2019)
The purpose of this study was to determine the effect of price, product quality and ease of purchasing decisions on Nexian mobile at the Lazada site (Study on STIE-AUB Surakarta students). This study uses a qualitative approach. The population in this study was 376 people. The sampling technique used is Accidental Sampling. The samples taken in this study were 25% of the total population, so the sample in this study was 100 people. The data analysis technique used is multiple linear regression. The results showed that product quality had a positive and significant effect on the purchasing decisions of the Nexian mobile online at the Lazada site, the price and convenience had a positive and insignificant effect on the purchasing decision for the Nexian mobile online at the Lazada site. Simultaneously the price variable, product quality and convenience together influence the purchasing decision. The ability of price variables, product quality and ease in influencing purchasing decisions as shown in Adjusted R Square is 58.4% while the remaining 41.6% is influenced by other factors not included in research models such as promotion, service quality, brand image, product reviews, and trust.